Analisis Implementasi Deep Learning dalam Pembelajaran Sains di Kelas VI Madrasah Ibtida’iyah: Perspektif Guru dan Siswa - Ananta, Luthfiah Nanda; Setyaningrum, Vidya (PIONIR: JURNAL PENDIDIKAN, 2026)
This study examines the implementation of a deep learning approach in sixth-grade science learning at Madrasah Ibtidaiyah Miftahul Ulum Pontianak Utara. Grounded in the demands of 21st-century education, deep learning emphasizes meaningful, reflective, and student-centered learning to enhance conceptual understanding and higher-order thinking skills. This research employed a qualitative case study design, with data collected through in-depth interviews with science teachers and supported by literature review. Data were analyzed descriptively to identify implementation patterns, challenges, and teacher strategies. The findings indicate that deep learning has begun to be implemented through the use of audio-visual media and discussion methods, which promote active engagement, critical thinking, and improved conceptual understanding among students. However, the implementation remains suboptimal due to several constraints, including limited teacher understanding, insufficient professional training, inadequate infrastructure, and variations in student participation. To address these challenges, teachers utilize instructional videos and structured discussions as adaptive strategies. The study highlights the need for continuous professional development, improved learning resources, and stronger institutional support to optimize deep learning practices. These findings provide practical insights for developing more effective, contextual, and student-centered science learning aligned with the Merdeka Curriculum. Keyword: Deep Learning, Science, Pedagogical Approach